2020
DOI: 10.1101/2020.01.06.895979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Invertebrate Metaxins 1 and 2: Widely Distributed Proteins Homologous to Vertebrate Metaxins Implicated in Protein Import into Mitochondria

Abstract: Metaxin 1 and 2 genes, previously investigated in vertebrates, are shown to be widely distributed among invertebrates. But metaxin 3 is absent. The predicted proteins of the invertebrate metaxins were initially identified by homology with human metaxin 1 and 2 proteins, and by the presence of characteristic GST_Metaxin protein domains. Invertebrate metaxins were revealed for a variety of phyla, including Echinodermata, Cnidaria, Porifera, Chordata, Arthropoda, Mollusca, Brachiopoda, Placozoa, and Nematoda. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The possession of GST_N_Metaxin and GST_C_Metaxin protein domains is a feature that defines the metaxin proteins and metaxin-like proteins. In addition, the Tom37 domain is a common feature of vertebrate metaxins including metaxin 3 (Adolph, 2019), invertebrate metaxins 1 and 2 (Adolph, 2020a), and bacterial metaxin-like proteins (Adolph, 2020b). In this study, protists of various taxa were found to contain a single metaxin-like protein, like plants and bacteria, and not homologs of the vertebrate and invertebrate metaxins.…”
Section: Conserved Protein Domains Of Protist and Fungal Metaxin-likementioning
confidence: 63%
See 3 more Smart Citations
“…The possession of GST_N_Metaxin and GST_C_Metaxin protein domains is a feature that defines the metaxin proteins and metaxin-like proteins. In addition, the Tom37 domain is a common feature of vertebrate metaxins including metaxin 3 (Adolph, 2019), invertebrate metaxins 1 and 2 (Adolph, 2020a), and bacterial metaxin-like proteins (Adolph, 2020b). In this study, protists of various taxa were found to contain a single metaxin-like protein, like plants and bacteria, and not homologs of the vertebrate and invertebrate metaxins.…”
Section: Conserved Protein Domains Of Protist and Fungal Metaxin-likementioning
confidence: 63%
“…The vertebrate metaxin 1 and 2 patterns of helices are also found for invertebrate metaxins 1 and 2 (Adolph, 2020a). Plant metaxin-like proteins have the vertebrate metaxin 1 pattern of nine helices (Adolph, 2020b).…”
Section: Alpha-helical Secondary Structures Of Protist and Fungal Metmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, metaxin proteins were detected among invertebrates such as the nematode C. elegans and the fruit fly Drosophila melanogaster. A broad range of invertebrate phyla were found to possess proteins homologous to vertebrate metaxins 1 and 2 (Adolph, 2020). The aim of the study reported here was to investigate whether proteins homologous to the metaxins also exist in plants and bacteria.…”
Section: Introductionmentioning
confidence: 99%